Pelatihan Pembelajaran Aktif, Kreatif, Inovatif, dan Menyenangkan (PAIKEM) pada Guru Sekolah Dasar di Kecamatan Padang Cermin, Kabupaten Pesawaran, Lampung - Siti Patimah; Deti Elice; Fahrina Yustiasari Liriwati; Eneng Muslihah (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
Active, Creative, Innovative and Fun Learning Training (PAIKEM) is a strategy designed to improve the quality of learning through an approach that involves students actively and creatively. This article aims to describe the implementation and results of PAIKEM training for elementary school teachers in Padang Cermin District, Pesawaran Regency, Lampung. Training was carried out in three stages: preparation, implementation and evaluation. The methods used include simulations, group discussions, and practical assistance in class. The results of the training show an increase in teachers' understanding of PAIKEM principles, increased skills in applying creative methods, and increased student participation in the learning process. This training makes a significant contribution to the development of teacher competence and the quality of learning in elementary schools. To ensure the sustainability of the impact of training, continued assistance and synergy between schools, government and the education community is needed.